Feed quantitative restriction and coenzyme Q10 level on performance, plasma lipoproteins and organ weights of broiler chicks - Jahanpour, H.; Chamani, M.; Seidavi, A.R.; Sadeghi, A.A.; Amin-Afshar, M. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
An experiment was conduct in order to investigate the effects of feed restriction level and duration and dietary coenzyme Q10 level on growth performance, organ characteristics and plasma lipoproteins. A factorial arangment based on a completely randomized design was performed using two levels of feed restriction (10 and 20% less than the standard Ross strain 308 guidelines), two levels of restriction duration (7 and 14 days) and three levels of coenzyme Q10 (0, 20 and 40 mg/kg feed). The results of the experiment showed that restriction intensity had significant effect on feed intake in first, second and sixth weeks of age (P<0.05), body weight gain in second and sixth weeks of age (P<0.05), and feed conversion ratio in first week of age (P<0.05). Restriction duration had significant effect on feed intake in third week of age (P<0.05), and feed conversion ratio in third and sixth weeks of age (P<0.05). Coenzyme Q level had significant effect on feed intake in first and sixth weeks of age (P<0.05), body weight gain in second, fifth and sixth weeks of age (P<0.05), and feed conversion ratio in second and sixth weeks of age (P<0.05).  In conclusion, considering the positive effects of feed restriction and coenzyme Q10 on broiler yield, the simaltaneous use of feed restriction strategy and dietary coenzyme Q10 can be considered as a management program in order to improvement of broiler productivity.